Molecular cloning and further characterization of rat peroxisomal trihydroxycoprostanoyl-CoA oxidase - Baumgart-Vogt, Eveline; Vanhooren, Johannes C. T.; Fransen, Mark; Van Leuven, Fred; Fahimi, H. Dariush; Van Veldhoven, Paul P.; Mannaerts, Guy P (Biochemical journal, 1996)
The composite trihydroxycoprostanoyl-CoA oxidase cDNA sequence, derived from overlapping clones isolated via screening of two different rat liver expression libraries, consisted of 2509 bases and contained an open reading frame of 2046 bases, encoding a protein of 681 amino acids with a calculated molecular mass of 76711 Da. The reading frame and identity of the trihydroxycoprostanoyl-CoA oxidase cDNA were confirmed by the location of various tryptic peptides, obtained from the purified enzyme, in the deduced amino acid sequence. The C-terminus (His-Lys-Met) of trihydroxycoprostanoyl-CoA oxidase did not seem to interact with the C-terminal peroxisomal targeting signal 1 (PTS1) import receptor, although the tripeptide fits the rule of conserved PTS1 variants for targeting of proteins to glycosomes of Trypanosomatidae. At the protein level, trihydroxycoprostanoyl-CoA oxidase showed 45% identical amino acids with rat palmitoyl-CoA oxidase, whereas the identity with pristanoyl-CoA oxidase was much lower (22%). Northern analysis of multiple rat tissues revealed a signal (approx. 2.6 kb) only in liver and (although much weaker) in kidney. Dot-blot analysis of total liver RNA revealed that the mRNA for trihydroxycoprostanoyl-CoA oxidase is not induced after treatment of rats with structurally unrelated peroxisome proliferators and indicates that highly similar mRNAs are present in other mammals, including man. Immunocytochemistry showed a decrease in trihydroxycoprostanoyl-CoA oxidase protein in individual liver peroxisomes (‘diluting-out effect’) after treatment of rats with bezafibrate, whereas the palmitoyl-CoA oxidase labelling was significantly increased.